Structural and Construct Validity of the Foot and Ankle Ability Measure (FAAM) With an Emphasis on Pain and Functionality After Foot Surgery: A Multicenter Study - Saarinen Antti J; Uimonen Mikko M; Suominen Eetu N; Sandelin Henrik; Repo Jussi P (Elsevier, 2022)
The Foot and Ankle Ability Measure (FAAM) is a patient-reported outcome measure that is available in several languages. We aim to assess the structural and construct validity of the FAAM with an emphasis on pain and functionality after foot surgery. The activities of daily living (ADL) and Sports subscales of the Finnish version of the FAAM were completed by 182 patients who underwent operative treatment for disorders of the foot. Convergent validity was assessed by principal component analysis using Spearman's correlation coefficient between the FAAM subscales and the principal components (Function-PC and Pain-PC) derived from validated patient-reported outcome measures. Subscales were studied for floor and ceiling effects, internal consistency and unidimensionality. Internal consistency was examined with Cronbach's alpha and the subscale structure with exploratory factor analysis. FAAM-ADL had high correlation with the Function-PC (r = 0.87, 95% confidence interval [CI] 0.81-0.91) and the Pain-PC (r = 0.75, 95% CI 0.65-0.83). FAAM-Sports had moderate correlation (r = 0.64, 95% CI 0.50-0.74) with the Function-PC and high correlation (r = 0.74, 95% CI 0.64-0.82) with the Pain-PC. No floor or ceiling effects were observed. Cronbach's alpha was 0.97 (95% CI 0.96-0.98) for the ADL and 0.93 (95% CI 0.91-0.95) for the Sports subscales. The results supported the unidimensionality of the FAAM-Sports. Within the ADL subscale, 3 factors were identified, suggesting a 3-factor model for the FAAM overall. Results highlighted the inter-relationship of pain and physical function. Further research on longitudinal validity is needed.